Hubungan kebiasaan konsumsi ultra-processed food dan lingkar pinggang terhadap tekanan darah dewasa 26-45 tahun di Puskesmas Kedungmundu - Kurniawati, Nuzulia Nur; Setyaningsih, Aryanti (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: In Indonesia, hypertension is major concern due to high mortality rate.  Changes in lifestyle affect the increase in blood pressure. Blood pressure above normal is caused by several factors, including high consumption of Ultra-Processed Food (UPF) and waist circumference.Objectives: To determine the relationship between UPF consumption habits and waist circumference to blood pressure in adults 26 - 45 years of age at Kedungmundu Health Centre.Methods: Quantitative-correlative analytic observational method with cross-sectional approach in the working area of Kedungmundu Health Center, in November 2024 – February 2025. The variables studied included UPF consumption habits with modified Food Frequency Questionnaire, waist circumference with metlin, and blood pressure with digital tensimeter.The sample was 71 respondents using purposive sampling technique, Data analysis was performed univariate analysis using frequency distribution and bivariate with Chi-Square test (α = 5%).Results: The results showed 49,3% of respondents often consumed UPF, the waist circumference measurement results showed 74,6% of respondents were obese, and 67,6% of respondents had abnormal blood pressure. Statistical tests show there is no relationship between UPF consumption habits and blood pressure (p-value = 0,063. There is a relationship between waist circumference and blood pressure with a risk of 3,8 times greater than respondents who have a normal waist circumference size (p-value = 0,015; OR = 3,846).Conclusion: Waist circumference is related to adult blood pressure while UPF consumption habits are not related to increased adult blood pressure at Kedungmundu Health Centre.